A second-order TV-based coupling model and an ADMM algorithm for MR image reconstruction - Zhou, Bo; Yang, Yu-Fei; Hu, Bo-Xia (Zielona Góra: Uniwersytet Zielonogórski)
Motivated by ideas from two-step models and combining second-order TV regularization in the LLT model, we propose a coupling model for MR image reconstruction. By applying the variables splitting technique, the split Bregman iterative scheme, and the alternating minimization method twice, we can divide the proposed model into several subproblems only related to second-order PDEs so as to avoid solving a fourth-order PDE.
Keywords: MRI reconstruction; LLT model; LOT model; coupling model; ADMM; split Bregman; wavelet transform